Knowledge, Attitudes, and Practices Regarding Exclusive Breastfeeding among Lactating Mothers in Rural Bangladesh - Md Serajul Islam; Mustafa Sumon Al Rashid; ASM Abdur Rahman; Rowshon Ara Begum (KYAMC Journal, 2024)
Background: Exclusive breastfeeding stands at the forefront of maternal and child health, serving as a fundamental pillar for ensuring the optimal growth and development of infants. It not only acts as a crucial source of nutrition but also plays a pivotal role in fortifying the physical and cognitive well-being of newborns, while simultaneously fostering a profound bond between mothers and their infants. Objective: This research seeks to gauge the level of awareness among lactating mothers regarding the significance and benefits of exclusive breastfeeding. It aims to comprehend their attitudes towards exclusive breastfeeding (EBF) and scrutinize their actual practices in implementing this vital aspect of infant care. Materials and Methods: A cross-sectional study was conducted at the Department of Community Medicine, ASWMC, Jashore, in 2018. Data collection took place in the Outpatient Department (OPD) of 'Ad-din Sakina Medical College Hospital' and 'Mother & Child Welfare Centre, Jashore. Results: The study demonstrates a high awareness and adherence to exclusive breastfeeding, with 94.4% aware, 90.9% knowledgeable about recommended duration, 49.9% recognizing advantages, 14.6% aware of disadvantages, and a substantial majority (92.5%) practicing exclusive breastfeeding, though 7.5% do not. Conclusion: Bridging knowledge gaps, cultivating positive attitudes, and promoting consistent breastfeeding practices emerge as crucial components of a comprehensive strategy to boost exclusive breastfeeding rates. The collaboration between healthcare providers, policymakers, and the community is indispensable for the success of such initiatives, ultimately contributing to the overall health and well-being of both infants and lactating mothers. KYAMC Journal Volume: 15, No: 01, April 2024: 46-49.